THE ROLE OF FINANCIAL TECHNOLOGY IN ENHANCING THE EFFICIENCY OF FINANCIAL PERFORMANCE: AN APPLIED STUDY ON A SAMPLE OF SMALL AND MEDIUM ENTERPRISES - Qutayba Ibrahim Hamadeh (Scholar Express Journals, 2022)
The research focused on the role of financial technology in enhancing the efficiency of financial performance, where the research aims to know the nature of the relationship between financial technology and the extent of its impact on the efficiency of financial performance. Small and medium enterprises in Salah ElDin Governorate. According to the statistical treatment, the research reached a number of conclusions, the most important of which are: There is a direct, statistically significant relationship between financial technology (as an independent variable) and the efficiency of financial performance in the projects under research, as this ratio indicates that the greater the use of financial technology, the greater the efficiency of financial performance in The projects under research, as the research results proved that there is a statistically significant impact of financial technology on the efficiency of financial performance according to the percentages indicated in Table No. (5), thus it becomes clear the validity of the second hypothesis of the research, which states that “there is a positive and significant effect of financial technology on enhancing performance efficiency financial).
Keywords: Financial Technology; Financial Digital Technologies; Financial Performance Efficiency; Financial Performance Standards